Proposed Rules of Origin in Emerging Asia-Pacific Preferential Trade Agreements: Will PTAs Promote Trade and Development? - William E. James (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
World trade is increasingly being dominated by preferential trade agreements that have taken precedence over multilateral trade negotiations. Within Asia and the Pacific an explosion of bilateral deals is taking place that seems likely to produce a tangle of hub-spoke trade blocs centered on major Asian or Pacific countries.
Keywords: F1; 330; Rules of Origin; Preferential Trade Agreements